Kinderstärkende Pädagogik in der Grundschule im Kontext (post-)pandemischer Herausforderungen. Kennzeichen, Kritische Anfragen und Blinde Flecke. Vortrag an der Tagung: Was Resilienz stärkt. Chancen und Risiken eines immer populärer werdenden Konzepts. Pädagogische Hochschule Heidelberg. - Büker, Petra

KrafT: Bildungsdokumentation in der inklusiven Schule partizipativ gestalten. 9. Paderborner Grundschultag zum Thema: „Demokratie Lernen von Anfang an“. Online - Büker, Petra; Herding, Jana; Drexler, Leonie

Near-Term Effects of Short-Term Study Abroad: A Longitudinal Examination of Learner Perceptions - Müller, Mareike (Frontiers: The Interdisciplinary Journal of Study Abroad)
A relatively small body of research has been conducted on the near- and long-term effects of study abroad (SA) to date. This existing research suggests that SA effects on language skills tend to be volatile, while the impact on various aspects of learners’ personal, academic, and professional development may be longer-lasting. Yet, learner perspectives on the dynamics and durability of such effects, in particular in the context of short-term SA programs, remain largely unexplored. This study hence investigates the near-term impact of short-term SA programs as experienced by students within the first months and years following their sojourns. A qualitative case-study design is employed to examine the accounts of four American students of German, who studied abroad in Austria for four weeks and were interviewed repeatedly over a period of up to 40 months after their sojourns. The results suggest that, from the students’ perspective, many effects deteriorate in the near term, although the overall sojourn experience still appears influential. Abstract in German Nur wenige Forschungsvorhaben haben sich bislang den mittel- bis langfristigen Auswirkungen studentischer Auslandsaufenthalte gewidmet; die bisherige Datenlage deutet jedoch darauf hin, dass die Auswirkungen auf sprachliche Kompetenzen eher unbeständig sind, wohingegen die persönliche, studiums- und berufsbezogene Entwicklung der Lernenden länger von einem Auslandsaufenthalt beeinflusst wird. Die Dynamik und Beständigkeit derartiger Auswirkungen wurden jedoch kaum mit Blick auf kurze Auslandsaufenthalte (≤ acht Wochen) sowie aus der Perspektive der Studierenden erforscht, was die vorliegende Studie insbesondere hinsichtlich mittelfristiger Effekte fokussiert. Mittels eines qualitativen Fallstudiendesigns werden die Interviewdaten vier amerikanischer Deutschlernender untersucht, die sich vier Wochen in Österreich aufhielten und in einem Zeitraum von bis zu 40 Monaten nach ihrem Aufenthalt wiederholt befragt wurden. Die Ergebnisse zeigen, dass viele Auswirkungen eines solchen Aufenthalts aus studentischer Perspektive mittelfristig verblassen, auch wenn der Auslandsaufenthalt im Gesamten weiterhin als einflussreiche Erfahrung wahrgenommen wird.

Examining the Measurement Invariance and Convergent Validity of the SSIS-SELb-Student in Austria and Germany. 44th Annual Conference of the International School Psychology Association (ISPA) 2023. - Anthony, Christopher J.; Yost, M; Howe, A; Schwab, Susanne; Hassani, Sepideh; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Writing as Narrative Resource in Therapeutic Settings: Diaries, Sketches, Notes - Mildorf, Jarmila; Ketteler, Daniel (Narrative and Mental Health Today: Reimagining Theory and Practice)

Narrative and Mental Health: Reimagining Theory and Practice

Narratives and Mental Health: An Introduction - Mildorf, Jarmila; Punzi, Elisabeth; Singer, Christoph (Narrative and Mental Health: Reimagining Theory and Practice)

Universities and Academic Labour in Times of Precarisation and Digitalisation - Allmer, Thomas

Bootstrapping the Open Science culture: The fellowship approach - Heck, Tamara; Steinhardt, Isabel; Rahal, Rima-Maria; Schubotz, Moritz; Scholl, Dominik; Behrens, Sarah (Research Ideas and Outcomes)
Keywords: Open Science

Förderung der sozialen Partizipation von Kindern im inklusiven Unterricht. Workshop auf dem 9. Paderborner Grundschultag. Thema: „Demokratie von Anfang an! Demokratie in der Grundschule erfahren, mitgestalten und reflektieren“ - Görel, Gamze; Hellmich, Frank; Löper, Marwin Felix

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Narrative Experiments with Medical Categorization and Normalization in B. S. Johnson's House Mother Normal - Strauß, Sara (Narrative and Mental Health)

Please Mind the Gap. Reconfiguring Solidarity through Space in Michael Nicoll Yahgulanaas' Haida Manga Art. - Jende, Yvonne Kristin (Solidarités. Réseaux – Convivialités – Confrontations/ Solidarities. Networks – Convivialities – Confrontations, 44. Annual Conference of the Association for Canadian Studies in German-Speaking Countries)

Tax Education After WWII: How Spain, the USA, and West Germany Tried to Make Their Citizens Pay Honestly - Schönhärl, Korinna; Düll, Nasrin; Ramírez Lugo , Nadya Melina (Tax Evasion and Tax Havens since the Nineteenth Century)
State education in honest tax payment can be understood as a facet of training in citizenship, i.e. as an attempt by the modern state to standardize the behavior of its citizens and to prevent deviations. Based on this Foucauldian understanding, this exploratory article examines tax education in the United States, Spain, and West Germany from the mid-1940s to the late 1980s. During this period, the USA asserted itself as the champion of tax education and Spain consistently tried to emulate this example, albeit with more modest means and different semantic strategies from as early as the 1960s, when it was still under a autoritarian regime. The FRG, however, completely discontinued its few early attempts at tax education from the mid-1950s onwards. Even during the economic crises and tax scandals of the 1970s, there was no relaunch of the programs. The article locates the reasons for this highly uneven development in the different ideal images of the citizen in the three states.

Studien zu Schulleistungen und ihre Aufbereitung - Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Sonderpädagogik; Bildung; Bildungsstudien; Integration

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

Learning Computational Thinking in Secondary School (Year 8) in Germany in International Comparison: Results from ICILS 2018 - Labusch, Amelie; Eickelmann, Birgit (Teaching coding in K-12 schools: Research and application)

Die inhaltliche Ausgestaltung schulischer Medienkonzepte als Gelingensbedingung digitalisierungsbezogener Schulentwicklungsprozesse - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (Professionalisierung für digitale Bildung im Grundschulalter - Ergebnisse des Forschungsprojekts P3DiG)

Abschlussbericht zum Forschungsprojekt ‚Gelingensbedingungen und Transfer von erfolgreichen Digitalisierungsprozessen an Schulen in Nordrhein-Westfalen (GuTe DigiSchulen NRW) - Gerick, J.; Eickelmann, Birgit; Panten, B.; Rothärmel, A.; Rau, M.; Gottschalk, T.

Digitalisierungsbezogene Schulentwicklungsprozesse erfolgreich gestalten. Handreichung für die schulische Arbeit zu den Ergebnissen des Forschungsprojekts GuTe DigiSchulen NRW. - Gerick, J.; Eickelmann, Birgit; Rau, M.; Panten, B.; Rothärmel, A.; Gottschalk, T.